Prophetic Leadership of Kiai in Increasing Public Trust in Education at the Daaru Attauhid Islamic Boarding School, Kumpeh Ulu, Muaro Jambi - Ari Gunawan; Marwazi Marwazi; Kemas Imron Rosadi (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the concept of prophetic leadership applied by Kiai in increasing community trust in the Daaru Attauhid Islamic Boarding School. With a descriptive qualitative approach, this study collected data through in-depth interviews, participatory observations, and documentation analysis. The results of the study indicate that the prophetic leadership applied by Kiai includes honesty, responsibility, effective communication, and wisdom. These four aspects are applied in various strategies, such as increasing the credibility of the institution, improving the quality of leadership, and increasing community participation. In increasing community trust, Kiai also applies various strategies, such as social services, community involvement in Islamic boarding school decision-making, and improving the quality of education. The impact of this prophetic leadership is seen in the recognition and support of the community, strengthening harmonious relations between Islamic boarding schools and the sustainability of Islamic boarding schools in the long term. The results of this study confirm that the prophetic leadership of Kiai has a major contribution in strengthening the relationship between Islamic boarding schools and the community, and can be used as a leadership model for other Islamic educational institutions